2010
DOI: 10.1073/pnas.0908341107
|View full text |Cite
|
Sign up to set email alerts
|

Light changes the atmospheric reactivity of soot

Abstract: Soot particles produced by incomplete combustion processes are one of the major components of urban air pollution. Chemistry at their surfaces lead to the heterogeneous conversion of several key trace gases; for example NO 2 interacts with soot and is converted into HONO, which rapidly photodissociates to form OH in the troposphere. In the dark, soot surfaces are rapidly deactivated under atmospheric conditions, leading to the current understanding that soot chemistry affects tropospheric chemical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
262
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(278 citation statements)
references
References 46 publications
12
262
1
3
Order By: Relevance
“…This value is much lower than that on soot samples. 4 Therefore, the contribution of the heterogeneous reaction of NO 2 on mineral dust to tropospheric HONO might be negligible under typical atmospheric conditions. However, the mass loading of dust is often increased on severe haze days.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is much lower than that on soot samples. 4 Therefore, the contribution of the heterogeneous reaction of NO 2 on mineral dust to tropospheric HONO might be negligible under typical atmospheric conditions. However, the mass loading of dust is often increased on severe haze days.…”
Section: Conclusion and Atmospheric Implicationsmentioning
confidence: 99%
“…9,10 For example, heterogeneous reactions of NO x on soot and mineral dust can produce gaseous HONO, 3,4,11 which is a daytime source of OH radicals; 12 while reactions between NO x and sea salt might be a source of Cl radicals. 10 Mineral dust is an important component of APM, with a loading of 1000-3000 Tg per year.…”
Section: Introductionmentioning
confidence: 99%
“…93 However, recent work has provided strong constraints on the unknown HONO daytime source and its relation to NO 2 chemistry. 26 Key ndings were that the rates of HONO production during daytime, R HONO , at a given site (1) are an order of magnitude faster than extrapolated nighttime rates of the hydrolytic disproportionation of NO 2 on wet surfaces, 27 (2) systematically increase with solar ux, peaking at noon but, however, (3) can be accounted neither by the reaction of excited NO 2 * with H 2 O(g), 28 reaction R9 nor by the reduction of NO 2 photosensitized by irradiated soot, [C-H] red *, reaction R10: 46,94 …”
Section: Observational Constraints On the Unknown Hono Daytime Sourcementioning
confidence: 99%
“…Measured mixing ratios are typically about 1 order of magnitude higher than simulated ones, and an additional source of 200-800 ppt h −1 would be required to explain observed mixing ratios Acker et al, 2006;Li et al, 2012;Su et al, 2008;Elshorbany et al, 2012;Meusel et al, 2016), indicating that estimates of daytime HONO sources are still under debate. It was suggested that HONO arises from the photolysis of nitric acid and nitrate or by heterogeneous photochemistry of NO 2 on organic substrates and soot (Zhou et al, 2001(Zhou et al, , 2002(Zhou et al, and 2003Villena et al, 2011;Ramazan et al, 2004;George et al, 2005;Sosedova et al, 2011;Monge et al, 2010;Han et al, 2016). Stemmler et al (2006Stemmler et al ( , 2007 found HONO formation on light-activated humic acid, and field studies showed that HONO formation correlates with aerosol surface area, NO 2 and solar radiation (Su et al, 2008;Reisinger, 2000;Costabile et al, 2010;Wong et al, 2012;Sörgel et al, 2015) and is increased during foggy periods (Notholt et al, 1992).…”
Section: Introductionmentioning
confidence: 99%